GhWRKY33 Interacts with GhTIFY10A to Synergistically Modulate Both Ageing and JA-Mediated Leaf Senescence in Arabidopsis - Songguo Wu; Huimin Zhang; Ruling Wang; Guimei Chang; Yifen Jing; Zhifang Li; Ligang Chen (Cells, 2022)
WRKY transcription factors play critical roles in the modulation of transcriptional changes during leaf senescence, but the underlying mechanisms controlled by them in this progress still remain enigmatic. In this study, Gossypium hirsutum WRKY DNA-binding protein 33 (GhWRKY33) was characterized as a negative regulator of both ageing and JA-mediated leaf senescence. The overexpression of GhWRKY33 in Arabidopsis greatly delayed leaf senescence, as determined by elevated chlorophyll content, lower H2O2 content, and reduced expression of several senescence-associated genes (SAGs). An electrophoretic mobility shift assay (EMSA) and transient dual–luciferase reporter assay revealed that GhWRKY33 could bind to the promoters of both AtSAG12 and Ghcysp and suppress their expression. Yeast two-hybrid (Y2H) and firefly luciferase complementation imaging (LUC) assays showed that GhWRKY33 could interact with GhTIFY10A. Similarly, the overexpression of GhTIFY10A in Arabidopsis also dramatically delayed leaf senescence. Furthermore, both GhWRKY33 and GhTIFY10A negatively regulate JA-mediated leaf senescence. In addition, a transientdual-luciferase reporter assay indicated that GhWRKY33 and GhTIFY10A could function synergistically to inhibit the expression of both AtSAG12 and Ghcysp. Thus, our work suggested that GhWRKY33 may function as a negative regulator to modulate both ageing and JA-mediated leaf senescence and also contributes to a basis for further functional studies on cotton leaf senescence.